Home pharmacological therapy in early COVID‐19 to prevent hospitalization and reduce mortality: Time for a suitable proposal. Issue 2 (2nd December 2021) - Pandolfi, Sergio; Chirumbolo, Salvatore; Ricevuti, Giovanni; Valdenassi, Luigi; Bjørklund, Geir; Lysiuk, Roman; Doşa, Monica Daniela; Lenchyk, Larysa; Fazio, Serafino
Abstract: The COVID‐19 pandemic is a highly dramatic concern for mankind. In Italy, the pandemic exerted its major impact throughout the period of February to June 2020. To date, the awkward amount of more than 134, 000 deaths has been reported. Yet, post‐mortem autopsy was performed on a very modest number of patients who died from COVID‐19 infection, leading to a first confirmation of an immune‐thrombosis of the lungs as the major COVID‐19 pathogenesis, likewise for SARS. Since then (June–August 2020), no targeted early therapy considering this pathogenetic issue was approached. The patients treated with early anti‐inflammatory, anti‐platelet, anticoagulant and antibiotic therapy confirmed that COVID‐19 was an endothelial inflammation with immuno‐thrombosis. Patients not treated or scarcely treated with the most proper and appropriate therapy and in the earliest, increased the hospitalization rate in the intensive care units and also mortality, due to immune‐thrombosis from the pulmonary capillary district and alveoli. The disease causes widespread endothelial inflammation, which can induce damage to various organs and systems. Therapy must be targeted in this consideration, and in this review, we demonstrate how early anti‐inflammatory therapy may treat endothelia inflammation and immune‐thrombosis caused by COVID‐19, by using drugs we are going to recommend in this paper.